The Importance of Geographic Access for the Impact of Microfinance - Nargiza Alimukhamedova; Randall Filer; Jan Hanousek (Center for Economic Studies and ifo Institute (CESifo), 2015)
The geographic distance between a household and financial institutions may constitute a significant obstacle to achieving the benefits of modern financial institutions. We measure the impact of improved distance-related access to microcredits in Uzbekistan. Residents living closer to microfinance institutions are propensity score matched to those further away using both household and village characteristics. Households located closer to microfinance institutions have larger businesses in terms of income, profits and employees than similar households located further away. Similarly, they spend more on most forms of consumption and have greater savings.
Keywords: O16; C34; 330; microcredit; microfinance institutions; geographic access